System characteristics of the publishing process - Ю. О. Морщавка (Ринкова економіка: сучасна теорія і практика управління)
The article deals with the systemic characteristics of the publishing process in the publishing industry of the national economy. The stages of the modern publishing process in the publishing industry are explored. The application of the system approach, which provides an opportunity to carry out research of the management process in the publishing industry, is considered, taking into account not only the individual individuality of any element, but also their functioning in the interconnection under the influence of macroeconomic and microeconomic factors. The optimal combination of elements of the internal environment in the publishing process is substantiated. Formulated principles that provide the optimal combination of elements of the internal environment in the publishing process. The functional segments of the internal environment of the publishing process are determined. The direction of analytical and informational support in the publishing process is singled out. The synthesized substantiation of the development potential of the publishing industry is developed. It is substantiated that the efficiency of the publishing process can be increased due to the coordination of the coordination and regulation paradigm.